Acne therapy in adolescent children - Yu. N. Perlamutrov; K. B. Olkhovskaia; A. O. Lyapon (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Current knowledge of the pathogenesis of acne determines the need for early use of drugs with antiinflammatory activity.Aim: to determine the effectiveness of monotherapy using Adaklin cream in the treatment of acne in adolescent children.Material and methods. All adolescents with acne of light and moderate severity were examined to determine the dermatological index of acne (DIA), determine the level of production of sebaceous glands, testing the parents of patients. Monotherapy was performed using Adaklin cream.Results. 60 patients with acne were under observation. Formation of clinical remission was registered in 78.33 % of adolescents. A good tolerability of the therapy and a high level of compliance were noted.Conclusion: the high efficacy and tolerability of therapy with the use of Adaklin cream in adolescents with acne was stated.